2013
DOI: 10.1002/tea.21087
|View full text |Cite
|
Sign up to set email alerts
|

Science as a classed and gendered endeavor: Persistence of two white female first‐generation college students within an undergraduate science context

Abstract: As colleges and universities aim for greater diversity in their undergraduate populations, one population researchers consider is first‐generation students, or students whose parents do not have a college education. The research reported here addresses first‐generation college students' discipline of study (e.g., biology) and its impact on their persistence. Exploring how female, low‐income, first‐generation college students evaluate their persistence within undergraduate science learning environments contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
3
34
0
2
Order By: Relevance
“…We respectfully disagree. As Wilson and Kittleson () state in relation to their use of participant narratives, the focus on participant‐relayed details about their own experiences is helpful to “…gain insight into the dynamic between the narratives…used to explain their experiences (agency), narratives used to position them in their context (structure), and the consequences of these cultural narratives for the participants' interpretation of their own persistence within science” (pp. 808–809).…”
Section: Methods and Analysismentioning
confidence: 99%
“…We respectfully disagree. As Wilson and Kittleson () state in relation to their use of participant narratives, the focus on participant‐relayed details about their own experiences is helpful to “…gain insight into the dynamic between the narratives…used to explain their experiences (agency), narratives used to position them in their context (structure), and the consequences of these cultural narratives for the participants' interpretation of their own persistence within science” (pp. 808–809).…”
Section: Methods and Analysismentioning
confidence: 99%
“…For example, a woman who is African American likely faces challenges in her pursuit of a science degree that differ from the challenges faced by a woman who is European American. Although several qualitative studies provide rich insight into the experiences of individuals who identify with multiple marginalized groups (e.g., Johnson, 2007;Wilson & Kittleson, 2013), this work would be bolstered by large-scale quantitative and mixed-methods studies that make targeted comparisons between participants who differ on the basis of crosscutting social identities. Indeed, research conducted with African American youth suggests that an intersectionality framework may help to explain variation in academic outcomes among college and graduate students (e.g., Wood, Kurtz-Costes, & Copping, 2011).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, neither Crisp et al (2009) in their study on STEM nor Hartman and Hartman (2006) in their single-institution study on engineering found first-generation status to influence a students' likelihood of persisting in the major. Wilson and Kittleson (2013) offered conclusions based on a qualitative study of two women FGCSs in STEM majors. They found that these first-generation, low-income, women in STEM majors perceived challenges of not being positioned to "compete" in these majors due to culturally based priorities.…”
Section: Underrepresented Populations In Stemmentioning
confidence: 99%